2016
DOI: 10.1007/s11307-016-0982-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Brain Biodistribution of the Lipoprotein-Associated Phospholipase A2 (Lp-PLA2) Inhibitor [18F]GSK2647544 in Healthy Male Subjects

Abstract: PurposeGSK2647544 is a potent and specific inhibitor of lipoprotein-associated phospholipase A2 (Lp-PLA2), which was in development as a potential treatment for Alzheimer’s disease (AD). In order to refine therapeutic dose predictions and confirm brain penetration, a radiolabelled form of the inhibitor, [18F]GSK2647544, was manufactured for use in a positron emission tomography (PET) biodistribution study.Procedures[18F]GSK2647544 was produced using a novel, copper iodide (Cu(I)) mediated, [18F]trifluoromethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…According to the results, GSK2647544 is able to cross the blood brain barrier and enter the human brain. An exploratory analysis of the data indicated that a dose of 102 mg, twice daily would be sufficient to in-hibit~80% brain LpPLA 2 [126].…”
Section: Inhibitors Of Lipoprotein-associated Phospholipase Amentioning
confidence: 99%
“…According to the results, GSK2647544 is able to cross the blood brain barrier and enter the human brain. An exploratory analysis of the data indicated that a dose of 102 mg, twice daily would be sufficient to in-hibit~80% brain LpPLA 2 [126].…”
Section: Inhibitors Of Lipoprotein-associated Phospholipase Amentioning
confidence: 99%
“…Furthermore, GSK2647544 could likely penetrate into the brains of preclinical species, which was verified by positron emission tomography biodistribution studies using [ 18 F] radiolabeled GSK2647544. This clinical trial also found that a twice‐daily dose of 102 mg generated approximately 80% trough inhibition of brain Lp‐PLA2 activity at steady state according to an exploratory analysis . Taken together, preclinical and preliminarily clinical studies showed that GSK2647544 acted as a useful tool for determining the effects of brain Lp‐PLA2 inhibition.…”
Section: Identification Of Small‐molecule Inhibitors Of Lp‐pla2mentioning
confidence: 72%
“…This clinical trial also found that a twice-daily dose of 102 mg generated approximately 80% trough inhibition of brain Lp-PLA2 activity at steady state according to an exploratory analysis. 255 Taken together, preclinical and preliminarily clinical studies showed that GSK2647544 acted as a useful tool for determining the effects of brain Lp-PLA2 inhibition. However, another study reported that GSK2647544 might be a moderate to strong CYP3A4 inhibitor, suggesting potential adverse drug-drug interaction.…”
Section: Pyrimidone Derivativesmentioning
confidence: 99%
“…While carbon-based perfluorinated functional groups are commonplace in numerous pharmaceuticals,a grochemicals and, materials, 18 F-perfluorinated motifs are seldom used in PET imaging. [5,6] This discrepancy is ac onsequence of the non-trivial nature of the radiochemical synthesis of these 18 Fperfluorinated functional groups,c oupled with the isotopic dilution with fluorine-19 that is usually observed. This results in products of low molar activity (A m ), potentially limiting their application.…”
mentioning
confidence: 99%
“…To test this hypothesis,t he initial studies began by synthesizing arange of fluoroalkenyl(aryl)iodonium triflates, bearing the 2-thienyl, mesityl, and 4-methoxyphenyl groups, [19] which are amongst the most commonly employed arenes for the 18 F-fluorination of diaryliodonium salts (Table 1). It was found that the use of (2,2,6,6-tetramethylpiperidin-1-yl)oxidanyl (TEMPO) was critical for the reaction to proceed in good radiochemical purity (RCP;T able 1, entries 4,6,7,9). [20] Thef luoroalkenyl(4-methoxyphenyl)iodonium triflate was found to give the highest RCP of 51 AE 12 % (n = 3), in acetonitrile at 85 8 8C( [21] however, the application of their conditions in this instance was not beneficial (Table 1, entry 3).…”
mentioning
confidence: 99%